UHPLC in life sciences - Guillarme, Davy; Veuthey, Jean-Luc (RSC chromatography monographs, 2012)
Since its commercial introduction in 2004, UHPLC (Ultra-High Performance Liquid Chromatography) has begun to replace conventional HPLC in academia and industry and interest in this technique continues to grow. Both the increases in speed and resolution make this an attractive method; particularly to the life sciences and more than 1500 papers have been written on this strongly-evolving topic to date.